Eddy covariance observations and FAO Penman-Monteith modelling of evapotranspiration over a heterogeneous farmland area - Mariusz Siedlecki; Włodzimierz Pawlak; Krzysztof Fortuniak (Meteorologische Zeitschrift, 2022)
This work presents the characteristics of actual evapotranspiration obtained using the eddy covariance method and a comparison with the results of crop reference evapotranspiration determined based on the FAO‑56 Penman-Monteith formula. The results of measurements performed under conditions typical of Central and Southern Poland's agricultural landscape cover the years 2012–2019. The characteristics of latent heat flux (Qe$Q_e$), as compared to other components of the heat balance, show its rapid growth in spring well above the value of sensible heat (Qh$Q_h$). The Qe$Q_e$ values in the noon hours account for over 50 % of the available solar energy. In the summer season, the ripening of cereals and their harvesting result in quite a significant decrease in the value of Qe$Q_e$, which entails an increase in the value of Qh$Q_h$ and an increasing value of the Bowen ratio (exceeding 1 in August). A comparison of the results of the covariance measurements with the results obtained on the basis of the FAO‑56 methodology shows that they are fairly consistent, especially in May and June, i.e. the period of high precipitation and fully developed vegetation. The average monthly values of the crop coefficient Kc, determined as the ratio of actual and reference evapotranspiration, takes values close to 1. In July, August and September, on the other hand, reference evapotranspiration is much higher than the values obtained from measurements. The determined values of Kc range between 0.7 and 0.8.